Introduction — talking back to the enlightenment : practicing anti-racist teaching and learning in eighteenth-century British literature (Roundtable) - Ozment, Kate (2021)
Yaa Gyasi’s Homegoing begins with the story of two eighteenth-century Akan sis-ters—Effia and Esi—as they stand symbolically above and below a grate in a castle in Cape Coast. The women are half-sisters who never meet and are physically joined only in that moment, unknown to one another, before being separated by an ocean. Above the grate, Effia has just married James Collins, the white British governor of the fort. Effia lives in relative comfort but is separated from her family, culture, and practices and must confront the contradictory dehumanization of and attraction to Black Akan women.1 Navigating this precarious world is hazardous for Effia and the other wives, including Eccoah, who notes, “There are women down there [in the dungeons] who look like us, and our husbands must learn to tell the difference.”2 Below the grate, Esi has been sold into slavery and sits in muck and filth. She and the other women are stacked on one another, raped and assaulted, and beaten until they are moved to ships for transport to the Caribbean. While Effia shudders at the fates of the women, termed “cargo,” below,3 Esi is unable to imagine anything other than the horror of her present, which she refers to as the “Now.”4 The destruction of Esi’s con-scious ties to her history dominoes through the generations: her daughter Ness does not learn how to speak Twi or understand its ties to the Akan,5 and Ness’s grandson H does not receive a full name because his mother committed suicide when she was kidnapped and forced into slavery. Yet through the novel, Gyasi explores not only the destruction of the slave system but also the ability of diasporic Akan people to persist, thrive, and eventually come to a place of healing and return.